Efeito da fração acetato de etila do extrato de Eugenia uniflora na expressão global de proteínas durante a morfogênese Candida albicans - Silva, Walicyranison Plinio da (2017)
Under certain circumstances, Candida albicans may switch a colonizing to a infecting yeast, such as in oral candidiasis. Morphogenesis in C. albicans, besides its ability to combat the oxidative stress inside phagocytic cells is an essential step for tissue invasion and establishment of infection. Due to the reduced drug arsenal used for treatment of fungal infections and the constant emergence of resistant strains, it is mandatory to search for new therapeutic sources, mainly from natural products. In the present study, 48 clinical isolates of C. albicans from the oral cavity of renal transplant recipients were selected. In order to evaluate the comparative action (treated and untreated cellst) on phagocytosis and morphogenesis of C. albicans, the ethyl acetate fraction of Eugenia uniflora extract was used at a concentration of 1000 μg/mL. Resistance of C. albicans to polymorphonuclear neutrophils was carried out. The isolate 111R, a highly filamentous strain was used to evaluate protein profiling through proteomic analysis, as well as the interaction with proteins directly associated with morphogenesis. The in vivo response to infection was observed in murine model of oral candidiasis and the toxic action of E. uniflora extract was observed in the MTT assay. E. uniflora extract significantly reduced the phagocytosis of C. albicans (Mean 120.36 ± 36.71 vs. 44.68 ± 19.84). Thirty-nine proteins, related to energy generation, protein and glucose metabolism, cell division, cytoplasmic transport, nucleic acid metabolism, cell structure and stress response were identified with proteomics analysis. Important proteins directly related with cytoesqueleton formation were down regulated on treated cells. The infection in the oral cavity of the mice was established and it was attenuated when both C. albicans cells were either preincubated in the presence of E. uniflora extract or when the extract was applied to the surface of the oral cavity after infection. These results were consistent with the reduction in CFU countings (2.36 vs. 1.85 Log10 CFU/ml) and attenuation of tissue damages observed in the histopathologycal analysis. E. uniflora extract was non-toxic to human cells even at concentrations 8 fold hugher than the one used in the experiments. The ethyl acetate fraction of E. uniflora may act act damaging and metabolism essential proteinsmainly related to cellular structure, reducing the plastic capacity of filamentation and attenuating infection in a murine modell model, without causing any toxic effect on human cells, suggesting that it may be a future therapeutic alternative for the treatment of Candida infections.